2019
DOI: 10.1111/aas.13329
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for the management of delirium in critically ill patients—A protocol for a systematic review

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…DEX is a highly selective α 2 -adrenoceptor (α 2 -AR) and imidazoline receptor agonist, 18 has been widely used for sedation and analgesia in anesthesia as well as antihypertensive, anxiolytic, and anti-delirium. [19][20][21] DEX may lead to the temporary less food intake as a sedation during the initial 7 days posttreatment, after this kind of calming effect gradually reduce and disappear, namely, the mice developed a tolerance to the sedative effects of DEX, food intake will not different between Vehicle-and DEX-treated groups, the body weight continues to decline may be due to the inhibition of liver fatty acid synthesis by DEX, which resulted in a decrease in lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEX is a highly selective α 2 -adrenoceptor (α 2 -AR) and imidazoline receptor agonist, 18 has been widely used for sedation and analgesia in anesthesia as well as antihypertensive, anxiolytic, and anti-delirium. [19][20][21] DEX may lead to the temporary less food intake as a sedation during the initial 7 days posttreatment, after this kind of calming effect gradually reduce and disappear, namely, the mice developed a tolerance to the sedative effects of DEX, food intake will not different between Vehicle-and DEX-treated groups, the body weight continues to decline may be due to the inhibition of liver fatty acid synthesis by DEX, which resulted in a decrease in lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…DEX is a highly selective α 2 -adrenoceptor (α 2 -AR) and imidazoline receptor agonist, 18 has been widely used for sedation and analgesia in anesthesia as well as antihypertensive, anxiolytic, and anti-delirium in the intensive care unit. [19][20][21] DEX can exert its effects via activation of three α 2 -adrenoreceptor subtypes. α2A and α 2C -adrenoreceptor (α 2A -AR and α 2C -AR) located in presynaptic membrane, and regulate the release of neurotransmitter (norepinephrine) in the central nervous system (CNS), cause transient hypertension, hyperglycemia, and tachycardia, which form a negative feedback loop to reduce the release of norepinephrine by inhibiting α 2A -AR.…”
Section: Introductionmentioning
confidence: 99%
“…85 86 The method has previously been applied by our group in systematic reviews with meta-analysis on a wide range of healthcare topics. [87][88][89][90][91][92][93][94] A PRISMA-P checklist file is attached (online supplementary additional file 1).…”
Section: Methods and Analysismentioning
confidence: 99%
“…On the contrary, other meta-analysis indicated that dexmedetomidine may reduce delirium and duration of MV in patients after cardiac surgery when compared with propofol[47], or in patients undergoing non-invasive ventilation in no-cardiac ICU[48]. According to Maagaard et al[49], the evidence regarding the use of dexmedetomidine in the treatment of ICU-D is conflicting and sparse. As the authors designed an exhaustive protocol for a systematic review, their results could give us valuable information on the real effectiveness of the drug on delirium management[49].…”
Section: Evidence Based Medicine Findings On Pharmacological Preventimentioning
confidence: 99%
“…According to Maagaard et al[49], the evidence regarding the use of dexmedetomidine in the treatment of ICU-D is conflicting and sparse. As the authors designed an exhaustive protocol for a systematic review, their results could give us valuable information on the real effectiveness of the drug on delirium management[49]. Finally, there is more uncertainty on the efficacy of anticholinesterase inhibitors as a systematic review found that these drugs offer no benefit in terms of prophylaxis, or treatment of diagnosed delirium[50].…”
Section: Evidence Based Medicine Findings On Pharmacological Preventimentioning
confidence: 99%